Toothbrushing with vegetable oil: a clinical and laboratorial analysis. - Aguiar, Alciara Alice de Almeida; Saliba, Nemre Adas (FapUNIFESP (SciELO), 2004)
The dentifrices currently available in the marketplace contain many anticariogenic substances, fluoride and abrasives aimed to better clean the dental surface, remove dental plaque, improve salivary flow and its buffer capacity and reduce colonies of bacteria such as S. mutans, the causative agent of dental caries. The objective of this study was to evaluate the possibility of adequately removing dental plaque using an experimental almond oil dentifrice (Titoil) with no abrasives or antiplaque agents. This study was carried out with 80 volunteers, all of them 18-year-old recruits from the military training school of Araçatuba -- SP. Saliva sampling and dental plaque disclosing were undertaken both before and after 28 days of toothbrushing with a low abrasive dentifrice (Group 1: 40 volunteers) or with Titoil (Group 2: 40 volunteers). Statistical analysis of the results revealed that the experimental dentifrice (Titoil) did not interfere with salivary flow and reduced dental plaque more than the low abrasive dentifrice, improved the salivary buffer capacity and decreased salivary S. mutans (Caritest-SM) as much as regular dentifrices. It was concluded that if the dental industry replaces abrasive by vegetable oil in dentifrices, these will be more effective in maintaining oral health and will cause less dental abrasion.
Keywords: almond oil; toothpaste; vegetable oil; adolescent; analysis of variance; dental caries; drug effect; human; male; nonparametric test; saliva; secretion; Streptococcus mutans; tooth brushing; tooth disease; tooth plaque; Adolescent; Analysis of Variance; Dental Caries; Dental Plaque; Dental Plaque Index; Dentifrices; Humans; Male; Plant Oils; Saliva; Statistics, Nonparametric; Tooth Abrasion; Toothbrushing